The Profit Sharing Organization: An Effective Work Force Driven Organization - Haridas, R.; Ramadevi, V.; Vijay, L. (Prabandhan: Indian Journal of Management, 2012)
In the modern era, organizations face numerous problems in their day to day work life. HR managers and experts put in immense efforts to solve organizational issues, but the problems prevail in organizations. The major challengeable problems are employee turnover and employee grievances. Furthermore, the important need of any organization is employing and training a motivated employee for increasing work productivity. A Profit Sharing Organization is a novel organization that exists for an ideal and common goal, wherein, the employer and the employees work as family members, share the profits equally and enjoy more benefits. Thus, Profit Sharing Organizations exhibit less number of employee grievances, low employee turnover rate, high level of employee motivation and performance, proper employee maintenance and good relationship among employees, which shows the path for organizational growth. This paper highlights the major problems faced by a contemporary organization, and elucidates the advantages and opportunities available in a Profit Sharing Organization. The time period of the study was from September 2011 - February 2012.